A novel packaged outdoor air dehumidifier with exhaust air heat pump – Experiment and simulation. (25th November 2020) - Cao, Xiang; Yang, Chen; Sun, Zhao; Lu, Yue-Ming; Chang, Meng-Meng; Shao, Liang-Liang; Zhang, Chun-Lu
Highlights: Condenser and subcooler are separated in the novel exhaust air heat pump (EAHP). A unique return air dehumidification mode is implemented with the EAHP. Energy efficiency of the novel EAHP is superior to the conventional ones. Abstract: Outdoor air dehumidification is one of the key functions of the ventilation system. A small packaged ventilation system with a built-in exhaust air heat pump (EAHP) is becoming popular for residential use. However, the conventional EAHP has low dehumidification capability and energy efficiency because the restricted volume flow of exhaust air would lead to high condensing temperature. In this work, a novel EAHP with separation of subcooler and condenser is proposed for the packaged outdoor air dehumidifier. In the exhaust air duct, the return air first lowers the refrigerant liquid temperature in subcooler and then joins the bypass outdoor air to cool the condenser before exhaust. In this way, lower condensing temperature and lower liquid temperature before expansion valve can be achieved to improve both the dehumidification capability and energy efficiency. A functional prototype was designed and tested. It achieved the dehumidification capability of 78.2 kg/day and the cooling COP (coefficient of performance) of 3.65 under the rated conditions. Moreover, based on a validated model, simulations show that energy efficiency of the novel system is superior to that of the conventional ones under variable operating conditions except for low dehumidification load.